Examination of Digitalized Non-Heritage Apparel Design Using CLO3D: Case Study of Ningbo Gold and Silver Color Embroidery (International Journal of Scientific Research and Management (IJSRM), 2024)
Driven by the wave of digitalization and fashion, traditional handicrafts in intangible cultural heritage (ICH) have experienced a remarkable transformation in the existing social value coordinate system. On the one hand, as a key carrier of the historical and cultural memory of the nation and the state, intangible cultural heritage is faced with many challenges of preservation and inheritance; on the other hand, the rapid development of digital technology provides innovative solutions for the modernization of traditional arts. This paper uses Ningbo gold, silver and color embroidery as a case study to explore the application of CLO3D software technology in the design of nonheritage apparel products and shows nonheritage crafts through digital simulation technology, which is not only the future development direction of the apparel industry but also the reconstruction of the apparel form and the use of function, aiming to assess its impact on nonheritage protection and innovation and to find a new path for the digital inheritance of nonheritage.